2010
DOI: 10.1111/j.1745-459x.2010.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Lexicon of Brewed Coffee for Japanese Consumers, Untrained Coffee Professionals and Trained Coffee Tasters

Abstract: A sensory lexicon was developed for describing the characteristics of brewed coffee. A panel consisting of six untrained coffee professionals and four experienced trained coffee tasters generated 377 expressions in a sensory evaluation of 24 coffee samples selected from commercial 52 coffee types. Of these expressions, 127 terms (seven for appearance, 61 for aroma, 23 for taste/flavor, eight for mouthfeel and 28 for overall impression) were selected for the lexicon. Twelve selected assessors who did not have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 18 publications
0
50
0
Order By: Relevance
“…These terms are similar to those reported being used by trained panelists by Di Donfrancesco et al (). There are some similarities among these attributes an those of Hayakawa et al (), but there are a number of attributes used by those authors that are not found in this lexicon primarily because they overlap with other attributes, are vague or general in nature, or have connotations associated with pleasantness, which are not descriptive in nature. Similarly, some terms are similar to those of Seo et al (), but the present lexicon contains more specific flavor terms perhaps because the previous authors used mass‐media terms and consumers as well as trained panelists to develop the lexicon they proposed.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…These terms are similar to those reported being used by trained panelists by Di Donfrancesco et al (). There are some similarities among these attributes an those of Hayakawa et al (), but there are a number of attributes used by those authors that are not found in this lexicon primarily because they overlap with other attributes, are vague or general in nature, or have connotations associated with pleasantness, which are not descriptive in nature. Similarly, some terms are similar to those of Seo et al (), but the present lexicon contains more specific flavor terms perhaps because the previous authors used mass‐media terms and consumers as well as trained panelists to develop the lexicon they proposed.…”
Section: Resultsmentioning
confidence: 83%
“…In this project that was done with Set 1 samples. Researchers proposed terms based on previous work (Di Donfrancesco et al, ; Sanchez & Chambers, ) and literature was consulted to include more terms that had been used in previous sensory research (Bhumiratana et al, ; Hayakawa et al, ; Narain, Paterson, & Reid, ). At this point, additional, terms, definitions, and references were proposed by the panel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensory lexicons provide accurate and reproducible results for descriptive sensory analysis (Cherdchu, Chambers, & Suwonsichon, ) and constitute a tool for communication within panels and across diverse audiences (Hayakawa et al, ; Lawless & Civille, ). Its application to describe and compare the quality of hibiscus teas should, therefore, lead to a better understanding of the quality of existing products and suggest avenues for the development of new ones.…”
Section: Introductionmentioning
confidence: 99%
“…Sensory language to describe the texture and mouthfeel of commercial coffee has been developed by research from Japan and Korea and includes terms such as having body astringency, round, smooth, thick, coarse, grainy, rough, oily, and sticky, with overall impressions of being crisp, pure, non-persistent, clear, sharp, mild, round, soft, delicate, balanced, intense, strong, heavy, hard, light, neutral, monotonous, flat, simple and light, mellow, winey, rich, nippy, piquant, pungent, tangy, acrid, alkaline, easy to swallow and refreshing (Hayakawa et al, 2010, Seo et al, 2009). An Italian study on the sensory classification of espresso developed descriptors such as thick, lingering, fullmouthed, viscous, resistance to tongue-palate movements, syrupy, consistency, velvety, pasty/doughy, creamy, mouth-coating, smooth, round, clinging/tongue coating, particulate, bulky, rich/heavy (Navarini et al, 2004).…”
Section: Mouthfeel and Chemesthesismentioning
confidence: 99%